Factors affecting behavioral intention and use behavior on e-wallet services - Hyronimus Kevin Kurniawan; Dudi Anandya (Enrichment : Journal of Management, 2023)
The purpose of this research is to examine the factors that influence behavioral intention and use behavior in e-wallet services (Gopay, Ovo, Dana, Shopee Pay) in Indonesia. The research model used is to develop the previous research model (UTAUT2) with the addition of price value, perceived credibility, and lifestyle compatibility variables. Questionnaires were collected from 300 e-wallet users in Indonesia, after which the data was analyzed using Structural Equation Modeling (SEM) with data processing using Analysis of Structural Moments (AMOS) software. The results of the research show that performance expectancy (PE), effort expectancy (EE), facilitating conditions (FC), price value (PV), habit (H), perceived credibility (PC), and lifestyle compatibility (LC) are proven to be significant factors influencing behavioral intention (BI), which in turn significantly predicts e-wallet use behavior (UB). Meanwhile, social influence (SI) and hedonic motivation (HM) do not significantly influence behavioral intention (BI).